Preliminary structural design of coreless spoiler by topological optimization - Israr, Haris; Chwen, Teh; Latif, Ainullotfi; Wong, King; Rahimian Koloor, Seyed; Yidris, Noorfaizal; Yahya, Mohd (MDPI, 2022)
Most spoilers are made from a sandwich structure with a honeycomb component as its core. However, the honeycomb core is sensitive to water ingress, causing damage to the control surface due to its weak moisture-resistance behavior. This study aimed to conduct the design and analysis of an improved composite structure for a coreless spoiler. A spoiler design of an aircraft, the A320, was used for the case study. The weaknesses of a coreless spoiler were identified through finite element analysis via Abaqus software. Multi-spar and multi-rib designs were studied and compared for topological optimization. The variables used for evaluation were the Tsai–Hill failure index and the critical buckling load. The design with the most potential was considered for parametric optimization to obtain the most satisfactory configuration. The results showed that the upper skin of the spoiler without a honeycomb core failed the Tsai–Hill criteria. Furthermore, the results show that the multi-spar configuration outperformed the multi-rib configuration. The final multi-spar configuration achieved a mass reduction of 24% from the original spoiler and an additional 6% mass reduction by re-designing the internal structures without violating the design criteria. In conclusion, the weaknesses of the spoiler without a honeycomb core have been identified, and an improved design for a coreless spoiler has been proposed.